Wakaf Produktif dalam Perspektif Kitab Fathul Wahhab pada Mata Pelajaran Kitab di Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta: Productive Endowments in the Perspective of the Book of Fathul Wahhab on Book Subjects at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta - Iga Mutiara Hakiki; Egidhea Dwiyamti Putri; Rahma Ayu Aulia Wardhani; Kalya Lintang Rayhana; Siti Alfiah Assaadah (Litera Academica Publishing, 2025)
This study examines the concept and implementation of productive waqf from the perspective of the Fathul Wahhab book in the curriculum at Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta. The main problem is the underutilization of waqf land in Indonesia for productive purposes, despite waqf’s great potential as a community economic resource. The qualitative research method involved literature study, field observation, content analysis, and data triangulation from the Fathul Wahhab book and pesantren administrators. The results indicate that productive waqf aligns with classical fiqh principles emphasizing the preservation of principal assets and sustainable distribution of benefits. Fathul Wahhab highlights the crucial role of nazhir as both trustworthy and professional in managing productive waqf to maximize economic benefits for beneficiaries. Proper management of productive waqf can foster economic independence and support social and religious development in Indonesia.